1998
DOI: 10.1175/1520-0485(1998)028<0519:otuado>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

On the Utility and Disutility of JEBAR*

Abstract: The usefulness of the concept of JEBAR, the joint effect of baroclinicity and relief, in large-scale ocean dynamics is critically analyzed. The authors address two questions. Does the JEBAR term properly characterize the joint impact of stratification and bottom topography on the ocean circulation? Do estimates of the JEBAR term from observational data allow reliable diagnostic calculations? The authors give a negative answer to the first question. The JEBAR term need not give a true measure of the effect of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 11 publications
0
31
0
Order By: Relevance
“…We should mention that some of the relations in this section have previously been discussed in Olbers and Wübber (1991), Olbers et al (1992), Mertz and Wright (1992) and Cane et al (1998).…”
Section: Discussionmentioning
confidence: 54%
“…We should mention that some of the relations in this section have previously been discussed in Olbers and Wübber (1991), Olbers et al (1992), Mertz and Wright (1992) and Cane et al (1998).…”
Section: Discussionmentioning
confidence: 54%
“…This is of the order of the interpentadal changes estimated from hydrographic observations by Sato and Rossby (1995), but substantially smaller than the 30 Sv estimated by Greatbach et al (1991). However, doubts have been raised on the reliability of the latter calculation (Cane et al 1998).…”
Section: Summary and Discussionmentioning
confidence: 77%
“…Note, however, that serious doubts have been raised on the reliability of such a calculation with limited data (Cane et al 1998), which was furthermore based on a simplifying assumption (linearity, no mixing or Reynolds stresses) that may not apply to the GS region. Using a large number of hydrographic sections, Sato and Rossby (1995) estimated that the decrease in the baroclinic transport was 6 Sv for the same period of time, and they found that their best sample pentads were within 4 Sv of each other.…”
mentioning
confidence: 99%
“…In general, both the wind and slope torque terms represent sources of vorticity, while the speed torque and frictional dissipation terms represent sinks of vorticity. As neither stratification nor bottom pressure observations were available during the study period, the effects of barotropic and baroclinic pressure gradients (e.g., Huthnance 1984;Cane et al 1998) are neglected here.…”
Section: Vorticity Equationmentioning
confidence: 99%